2021
DOI: 10.1071/ah19090
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional workforce return on investment from sponsoring rural generalist-based training for medical students

Abstract: The objective of this case study was to examine and evaluate the retention of medical graduates for a hospital and health service partnering with a university to deliver a rural medical program. Eight cohorts of the Griffith Rural Medical Longlook program were followed for workforce outcomes, including both rural and local workforce outcomes for the Darling Downs Hospital and Health Service (DDHHS) and the region. The DDHHS partnered with Griffith Health for capital investment in the region, creating three mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, it was identified that this rural work was not always sustained [42] and that graduates had limited prior contact with the rural areas in which they were working [50]. Other models of rural training included a partnership between a university and a health service to deliver a rural training program, with research finding that graduates who had participated in the program were more likely to remain local for an internship, as well as following an internship [44]. Overall, rural training was supported as a predictor of rural practice [65][66][67]78,81,89].…”
Section: Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…However, it was identified that this rural work was not always sustained [42] and that graduates had limited prior contact with the rural areas in which they were working [50]. Other models of rural training included a partnership between a university and a health service to deliver a rural training program, with research finding that graduates who had participated in the program were more likely to remain local for an internship, as well as following an internship [44]. Overall, rural training was supported as a predictor of rural practice [65][66][67]78,81,89].…”
Section: Medicinementioning
confidence: 99%
“…Medicine: Gupta et al, 2019 [42], Herd et al, 2017 [43], Kitchener 2021 [44], Kwan et al, 2017 [45] [68] Nursing and allied health: Playford, Moran and Thompson 2020 [69] Acknowledgments: We thank Deakin University librarians, Jill Stephens, and Fiona Russell, for their assistance in reviewing the search strategies used for this review.…”
mentioning
confidence: 99%